Thrombosis and antiphospholipid antibody syndrome during acute Q fever: A cross-sectional study. Issue 29 (July 2017) - Million, Matthieu; Bardin, Nathalie; Bessis, Simon; Nouiakh, Nadia; Douliery, Charlaine; Edouard, Sophie; Angelakis, Emmanouil; Bosseray, Annick; Epaulard, Olivier; Branger, Stéphanie; Chaudier, Bernard; Blanc-Laserre, Karine; et al.
Abstract : Abstract: Q fever is a neglected and potentially fatal disease. During acute Q fever, antiphospholipid antibodies are very prevalent and have been associated with fever, thrombocytopenia, acquired heart valve disease, and progression to chronic endocarditis. However, thrombosis, the main clinical criterion of the 2006 updated classification of the antiphospholipid syndrome, has not been assessed in this context. To test whether thrombosis is associated with antiphospholipid antibodies and whether the criteria for antiphospholipid syndrome can be met in patients with acute Q fever, we conducted a cross-sectional study at the French National Referral Center for Q fever. Patients included were diagnosed with acute Q fever in our Center between January 2007 and December 2015. Each patient's history and clinical characteristics were recorded with a standardized questionnaire. Predictive factors associated with thrombosis were assessed using a rare events logistic regression model. IgG anticardiolipin antibodies (IgG aCL) assessed by an enzyme-linked immunosorbent assay were tested on the Q fever diagnostic serum. A dose-dependent relationship between IgG aCL levels and thrombosis was tested using a receiver operating characteristic (ROC) analysis. Of the 664 patients identified for inclusion in the study, 313 (47.1%) had positive IgG aCL and 13 (1.9%) were diagnosed with thrombosis. Three patients fulfilled the antiphospholipid syndrome criteria. After multiple adjustments, only positive IgG aCL (relative risk, 14.46 [1.85–113.14], P = .011) were independently associated with thrombosis. ROC analysis identified a dose-dependent relationship between IgG aCL levels and occurrence of thrombosis (area under curve, 0.83, 95%CI [0.73–0.93], P < .001). During acute Q fever, antiphospholipid antibodies are associated with thrombosis, thrombocytopenia, and acquired valvular heart disease. Antiphospholipid antibodies should be systematically assessed in acute Q fever patients. Hydroxychloroquine, which has been previously shown to antagonize IgG aCL pathogenic properties, should be tested in acute Q fever patients with anticardiolipin antibodies to prevent antiphospholipid-associated complications. Key Point: In addition to fever, thrombocytopenia and acquired valvular heart disease, antiphospholipid antibodies are associated with thrombosis during acute Q fever. Abstract : Supplemental Digital Content is available in the text